(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper investigates the complex intersection of identity, cultural heritage, and food in the experiences of second generation immigrants. Food, more than a necessity for survival, emerges as a rich cultural symbol that reflects belonging and alienation, continuity and rupture. Through an analysis of Jhumpa Lahiri’s The Namesake, this study examines how food becomes a site of negotiation between two competing worlds i.e America modernity and Bengali tradition. For characters such as Gogol, Mousumi and Sonia, the act of eating, cooking, or even refusing certain food mirrors the larger struggle of assimilation and cultural retention. On one hand, food serves as a tangible connection to the homeland and familial bond; on the other hand, it often marks assimilation in to American society. Thus, the kitchen table, the dining room, and the social gatherings around meals become symbolic battlegrounds where generational conflict, diasporic identity, and questions of belonging are played out. By foregrounding the symbolic role of food, this paper underscores how Lahiri portrays culinary practices as a theme of diasporic identity and generational conflicts.